2014
DOI: 10.1158/1055-9965.epi-13-0733
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Cancer Risk—A Systematic Review and Meta-analysis of the Epidemiological Evidence

Abstract: Iron has been suggested as a risk factor for different types of cancers mainly due to its prooxidant activity, which can lead to oxidative DNA damage. Furthermore, subjects with hemochromatosis or iron overload have been shown to have a higher risk of developing liver cancer. We have systematically reviewed 59 epidemiologic studies, published between 1995 and 2012, reporting information on total iron, dietary iron, heme iron, and biomarkers of iron status and cancer risk. Furthermore we conducted metaanalysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
199
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 292 publications
(220 citation statements)
references
References 110 publications
(104 reference statements)
12
199
2
7
Order By: Relevance
“…First, we focused our analysis on serum iron, one of several biomarkers of iron status, which may or may not correlate with body iron stores (4,36). A recent meta-analysis of 59 epidemiologic studies concluded that biomarkers of iron stores tend to be negatively correlated with cancer risk (37). It should be noted that our study did not aim to assess the correlation of cancer risk with body iron stores, but with serum iron.…”
Section: Discussionmentioning
confidence: 99%
“…First, we focused our analysis on serum iron, one of several biomarkers of iron status, which may or may not correlate with body iron stores (4,36). A recent meta-analysis of 59 epidemiologic studies concluded that biomarkers of iron stores tend to be negatively correlated with cancer risk (37). It should be noted that our study did not aim to assess the correlation of cancer risk with body iron stores, but with serum iron.…”
Section: Discussionmentioning
confidence: 99%
“…Meat is a source of not only protein and various vitamins and minerals, but also SFA (26) which are well known to be a major risk factor for various chronic diseases (27,28) . Moreover, haem iron and non-haem iron, or some carcinogenic compounds such as heterocyclic amines and polycyclic aromatic hydrocarbons in meat are suspected to increase cancer risk (29,30) . As in studies involving Western populations, consuming high amount of red meat was reported as a significant risk factor for cancer by a recent Korean cohort study (31) .…”
Section: Association Of Meat and Milk Consumption With Cancer And Metmentioning
confidence: 99%
“…Laboratory evidence of elevated iron stores can be an important predictor of cardiovascular diseases, diabetes, neurodegenerative diseases, and cancers [1][2][3]. Iron status is routinely evaluated by biochemical assays such as serum iron (SI), total iron-binding capacity (TIBC), and serum ferritin (SF).…”
mentioning
confidence: 99%